2017
DOI: 10.1039/c6nr08069c
|View full text |Cite
|
Sign up to set email alerts
|

Colloidal joints with designed motion range and tunable joint flexibility

Abstract: The miniaturization of machines towards the micron and nanoscale requires the development of joint-like elements that enable and constrain motion. We present a facile method to create colloidal joints, that is, anisotropic colloidal particles functionalized with surface mobile DNA linkers that control the motion range of bonded particles. We demonstrate quantitatively that we can control the flexibility of these colloidal joints by tuning the DNA linker concentration in the bond area. We show that the shape of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
81
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 36 publications
(83 citation statements)
references
References 35 publications
1
81
1
Order By: Relevance
“…Indeed, the unimpeded pivoting of colloidal junctions enable the relaxation of the aggregates towards a closepacked hexagonal lattice maximising particle-particle contacts [15]. The properties of "colloidal joints" formed from bilayer-coated particles, including their range of motion and flexibility, were then systematically characterised by Chakraborty et al [105]. By studying the interactions between cubic and spherical particles, the authors also demonstrated the effect of surface curvature.…”
Section: Self-assembly Of Emulsion Droplets and Solid Particles With mentioning
confidence: 99%
“…Indeed, the unimpeded pivoting of colloidal junctions enable the relaxation of the aggregates towards a closepacked hexagonal lattice maximising particle-particle contacts [15]. The properties of "colloidal joints" formed from bilayer-coated particles, including their range of motion and flexibility, were then systematically characterised by Chakraborty et al [105]. By studying the interactions between cubic and spherical particles, the authors also demonstrated the effect of surface curvature.…”
Section: Self-assembly Of Emulsion Droplets and Solid Particles With mentioning
confidence: 99%
“…Another series of experiments concern the use of colloids functionalized with surface mobile DNA linkers as building blocks . It was possible to create flexible CMs which are physically stable but reorganise in permanence at high speed (Figure a) . The sequence programmable folding of a plasmid by DNA staple strands, also called DNA origami, which allows one to design nanoscale DNA architectures with extensive shape control, has also been used to template the organization of DNA coated particles.…”
Section: Processes Based On Controlled Clusteringmentioning
confidence: 99%
“…[47,48] It was possible to create flexible CMs which are physically stable but reorganise in permanencea th igh speed (Figure 3a). [49] The sequence programmablef olding of ap lasmidb yD NA Figure 3. a) Schematic representation and confocal microscopy images of flexible CMs made from particles with mobile DNA linkers.…”
Section: Assistedbyp Hysicalorc Hemical Interactionsmentioning
confidence: 99%
See 2 more Smart Citations